Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Asset Pada PT. Garuda Indonesia Tbk - Mohamad Alfi Ramadhani; Askolani Askolani; Rita Tri Yusnita (Universitas Dehasen Bengkulu, 2024)
This research was conducted with the aim of finding out the influence of the Current Ratio and Debt to Equity Ratio on Return On Assets at PT. Garuda Indonesia Tbk. The method used in this research is the correlation method with a quantitative approach. The type of data used is secondary data. The population used in this research is the financial reports at PT. Garuda Indonesia Tbk, with a research sample of 13 financial report data per year for the 2011-2023 period and the sample determination technique used the Purposive Sampling method. The analytical tool used in this research is multiple regression using SPSS version 25. The research results show that the Current Ratio and Debt to Equity Ratio simultaneously have a significant effect on Return On Assets at PT. Garuda Indonesia Tbk. Current Ratio partially has a significant effect on Return On Assets at PT. Garuda Indonesia Tbk. Debt to Equity Ratio partially has no significant effect on Return On Assets at PT. Garuda Indonesia Tbk.